Eczema in early childhood is strongly associated with the development of asthma and rhinitis in a prospective cohort - von Kobyletzki, Laura B (BioMed Central, 2012)
BACKGROUND: This study aimed to estimate the association between eczema in early childhood and the onset of asthma and rhinitis later in life in children. METHODS: A total of 3,124 children aged 1–2 years were included in the Dampness in Building and Health (DBH) study in the year 2000, and followed up 5 years later by a parental questionnaire based on an International Study of Asthma and Allergies in Childhood protocol. The association between eczema in early childhood and the incidence of asthma and rhinitis later in life was estimated by univariable and multivariable logistic regression modelling. RESULTS: The prevalence of eczema in children aged 1–2 years was 17.6% at baseline. Children with eczema had a 3-fold increased odds of developing asthma (adjusted odds ratio [aOR], 3.07; 95% confidence interval (CI) 1.79–5.27), and a nearly 3-fold increased odds of developing rhinitis (aOR, 2.63; 1.85–3.73) at follow-up compared with children without eczema, adjusted for age, sex, parental allergic disease, parental smoking, length of breastfeeding, site of living, polyvinylchloride flooring material, and concomitant allergic disease. When eczema was divided into subgroups, moderate to severe eczema (aOR, 3.56; 1.62–7.83 and aOR, 3.87; 2.37–6.33, respectively), early onset of eczema (aOR, 3.44; 1.94–6.09 and aOR, 4.05; 2.82–5.81; respectively), and persistence of eczema (aOR, 5.16; 2.62–10.18 and aOR, 4.00; 2.53–6.22, respectively) further increased the odds of developing asthma and rhinitis. Further independent risk factors increasing the odds of developing asthma were a parental history of allergic disease (aOR, 1.83; 1.29–2.60) and a period of breast feeding shorter than 6 months (aOR, 1.57; 1.03–2.39). The incidence of rhinitis was increased for parental history of allergic disease (aOR, 2.00; 1.59–2.51) and polyvinylchloride flooring (aOR, 1.60; 1.02–2.51). CONCLUSION: Eczema in infancy is associated with development of asthma and rhinitis during the following 5-year period, and eczema is one of the strongest risk factors. Early identification is valuable for prediction of the atopic march.